The energy substrate switch during cardiac development, with the onset of cardiac hypertrophy and the transition to heart failure. : delineation and characterisation of gene regulatory mechanisms : "changing concepts of metabolic regulation in the h - Sack, Michael N (Department of Medicine, 2014)
Bibliography: leaves 168-190.